2020
DOI: 10.20944/preprints202004.0272.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<strong></strong><strong>Anosmia and Ageusia as Initial or Unique Symptoms after SARS-COV-2 Virus Infection</strong>

Abstract: SARS-CoV-2 (CoV-2) is a coronavirus which is causing the actual COVID-19 pandemic. The disease caused by 2019 new coronavirus (2019-nCoV) was named coronavirus disease-19 (COVID-19) by the World Health Organization in February 2020. Primary non-specific reported symptoms of 2019-nCoV infection at the prodromal phase are malaise, fever, and dry cough. The most commonly reported signs and symptoms are fever (98%), cough (76%), dyspnea (55%), and myalgia or fatigue (44%). Nonetheless, recent reports suggest an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 104 publications
(120 reference statements)
2
24
0
1
Order By: Relevance
“…[75][76][77] It has been widely supported that that lesions in the medulla can cause respiratory dysfunction, like in congenital central hypoventilation syndrome, 78 or severe brain injury, 79 which results in damage to medullar respiratory control function. 35,[80][81][82][83][84] It is extremely important to remark that the brainstem has been severely infected by SARS-CoV34, 35 or MERS-CoV. It has been reported that viral antigens have been detected in the brainstem, where the infected regions included the nucleus of the solitary tract and nucleus ambiguous.…”
Section: Brainstem Dysfunction In Sars-cov-2 Infection As a Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…[75][76][77] It has been widely supported that that lesions in the medulla can cause respiratory dysfunction, like in congenital central hypoventilation syndrome, 78 or severe brain injury, 79 which results in damage to medullar respiratory control function. 35,[80][81][82][83][84] It is extremely important to remark that the brainstem has been severely infected by SARS-CoV34, 35 or MERS-CoV. It has been reported that viral antigens have been detected in the brainstem, where the infected regions included the nucleus of the solitary tract and nucleus ambiguous.…”
Section: Brainstem Dysfunction In Sars-cov-2 Infection As a Potentialmentioning
confidence: 99%
“…9-11, 13, 19, 25-34 We have recently reviewed that anosmia and hypogeusia as significant alerting initial or unique symptoms of COVID-19. 35 Curiously, neurotropic and neuro-invasive capabilities have been described in several of their hosts, including humans among them, leading to symptoms such as multiple sclerosis (MS) and encephalomyelitis. A rising amount of evidence demonstrates that neurotropism is one shared feature of CoVs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the natural origin for SARS-CoV-2 is a bat [2][3][4][5][6]. Coronavirus disease (COVID- 19) is an infectious disease ranging from a mild to more severe respiratory disease, common respiratory manifestations of COVID-19 is dry cough, fever, dyspnea, arthralgia and malaise [2,3], and less common symptoms such as nausea, vomiting, diarrhea and abdominal pain [7], is transmitted by person-to-person [2,3]. However, in several countries such as South Korea, China, Iran and Italy reported taste and smell dysfunctions in COVID-19 infection [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…Permanent smell disorders are induced by viral upper respiratory tract infections [11]. Current studies among patients show a relationship between COVID-19 infection and smell disorders (hyposmia, anosmia) and loss of taste (ageusia), however, olfactory disorder to be more prevalent than gustatory dysfunctions [2,12]. According to some reports, patients with COVID-19 infection show an entire or little loss of taste and smell [13], without rhinorrhea or nasal obstruction [10].…”
Section: Introductionmentioning
confidence: 99%
“…82 It can lead to neurological damage to the CNS which might be followed by anosmia and dysgeusia in COVID-19 patients; anosmia can also be caused by swelling in the nose and sinuses due to chronic sinusitis. 82 Some investigations claim that the proportion of ACE2expressing cells in nasal and oral tissue is comparable to the lung tissue. 83 It has been illustrated that olfactory epithelial support cells, stem cells, and nasal respiratory epithelium express TMPRSS2 and ACE2 genes by which SARS-CoV-2 can enter into them.…”
Section: Digestive System Manifestationsmentioning
confidence: 99%